A complicated clinical problem: surgical treatment decisions for patients with early-stage lung cancer - Shen, Jianfei; Liu, Yang; Dai, Chengyang; Chen, Baofu; Chen, Chang; Rocco, Gaetano; Brunelli, Alessandro; Liu, Chia-Chuan; Petersen, Rene Horsleben; He, Jianxing; AME Thoracic Surgery Collaborative Group, Written on behalf of the (Journal of Thoracic Disease, 2016)
Toste et al. raise several concerns in their editorial. To our knowledge, the forthcoming eighth edition of TNM classification proposed that T1 disease could subdivided into T1a (≤1 cm), T1b (>1 to 2 cm) and T1c (>2 to 3 cm) (1). This suggests that the size of tumor becomes a more important factor for the prognosis of early stage lung cancer. Not only the subdivision into 2 cm, but in addition, a recognition of the importance of component within the tumour, both clinically and pathologically by IASLC (2). In recent years, early CT screening for lung cancer has detected an increasing number of tumors, most of which have been small lung nodules (≤2 cm).